2005
DOI: 10.1680/macr.2005.57.8.433
|View full text |Cite
|
Sign up to set email alerts
|

CARDIFRC® – Development and mechanical properties. Part III: Uniaxial tensile response and other mechanical properties

Abstract: Part III of this three-part paper about CARDIFRC 1 , a class of high performance short steel fibre-reinforced cementitious composites (HPFRCCs), deals with the measurement of the tensile response of CARDIFRC 1 mixes on a specially developed specimen geometry and loading arrangement. It also compares the measured mechanical properties (Young's modulus, E, compressive strength, f c , tensile strength, f t , specific fracture energy, G F ) with the theoretically predicted values using micromechanical relations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(30 citation statements)
references
References 17 publications
2
22
0
1
Order By: Relevance
“…The comparison of load-deflection behaviour at 0% fibre volume (refer to Fig. 15) showed that the addition of metakaolin resulted in the highest flexural strength and corresponding deflection due to higher reactivity of metakaolin as mentioned in [27,28]. The load-deflection curve of FRC containing 1%, 2%, and 3% volume of the PVA fibres are presented in Figs.…”
Section: Load-deflection Behaviour and Tensile Strainmentioning
confidence: 93%
See 1 more Smart Citation
“…The comparison of load-deflection behaviour at 0% fibre volume (refer to Fig. 15) showed that the addition of metakaolin resulted in the highest flexural strength and corresponding deflection due to higher reactivity of metakaolin as mentioned in [27,28]. The load-deflection curve of FRC containing 1%, 2%, and 3% volume of the PVA fibres are presented in Figs.…”
Section: Load-deflection Behaviour and Tensile Strainmentioning
confidence: 93%
“…The reason for mode ''I" failure is the application of single point load at the middle centre of the beam span, as mentioned by [26]. It is also stated by Benson and Karihaloo [27] that multiple cracking will not be observed due to weakest point at the middle zone in the case of notched specimen. The data required for flexural testing was failure load, failure modes and complete load deflection response of all the beams along with strain results, which are presented in Table 5.…”
Section: Flexural Strengthmentioning
confidence: 98%
“…UHPFRCCs are defined as a concrete matrix with a typical strength of 150 MPa to 200 MPa in compression, 7 MPa to 15 MPa in uniaxial tension, and 25 MPa to 40 MPa in bending [5][6][7][8]. UHPFRCCs also exhibit high energy absorption capacity [9] and strain hardening under tension [5,10].…”
Section: Introductionmentioning
confidence: 99%
“…Though the fiber reinforced concrete (FRC) achieves much better properties than concrete, corresponding crack width still can not be effectively controlled and the material still shows tensile softening properties at common fiber volume fractions, which is usually less than 2%. Even the so called high performance fiber reinforced cementitious composites (HPFRCC), such as SIFCON [1] , SIMCON [2] and CARDIFRC [3] , show tensile strain capability of less than 1.5%. The corresponding crack widths are in the order of several hundred microns which may be too wide for many applications.…”
Section: Introductionmentioning
confidence: 99%